Anaemia in surgical patients and its effect on recovery of patients - Sonwani, Bharat; Singh, Krishna Kumar; Meshram, Sunita (International Surgery Journal, 2016)
Background: People who are anemic develop symptoms caused by the inadequate delivery of oxygen to their body tissues. This can vary from simple fatigue to death according to the nature and severity of the anaemia. In presence of anaemia, there are increased chances of morbidity and mortality resulting to a loss of the individual is particulars and nation at large. Anaemia in one, such, which the surgeons have had to deal with in promoting convalescence and healing in every day, practice. Prior knowledge of wound healing capacity in-patients with various surgical diseases is of great importance in the selection of appropriate treatment and for the prognosis of the patients. Methods: The present study was carried out in the Department of Surgery, S.S. Medical College and associated Gandhi Memorial Hospital, Rewa (M.P.) the material for the study comprised of randomly selected 200 anemic patients, during the period from 1st September 2000 to 31st June 2001. Patients admitted in routine or emergency time thoroughly interrogated for personal information. A thorough clinical examination was done to assess general condition of patients and systemic disorder. In case of surgical emergency arrival of the patient clinical examination was immediately started and history asked during the resuscitation of the patient. Patients were investigated either previously or after admission with special reference to haemoglobin, blood group and relevant investigations according to clinical diagnosis like x-ray, Ultrasonography, biopsy and prepared for surgical intervention as required. The line of treatment whether conservative or operative was also recorded in detail dates wise. All details of blood transfusion to the patient, pre-operative or post-operative were recorded date wise. Results: Majority of anemic patient were of malignancy (41%). Next common group of hemorrhoid (21.5%), minimum cases were for infected wound (7.5%).The incidence of malignancy and severity of anaemia both were more in female as compared to male. Study subjects were distributed nearly equal numbers between age 31 to above 60 yr. It was observed that severity of anaemia increased with the percentage of burn. Impairment of wound healing was noted in moderate degree of anaemia (6-10.9%), superficial gapping 40% incomplete dehiscence 8% was noted and severe anaemia (below 6 gm % Hb) all the cases noted complete dehiscence. Majority of the cases 67-87% were infective groups belongs to moderate and severe degree of anaemia. Conclusions: Anaemia in surgical patients can be prevented by early diagnosis and treatment of lesion where bleeding is present.